Speed control of a matrix converter excited doubly-fed induction machine - Shapoval, I.A.; Clare, J.C. (Технічна електродинаміка, 2011)
Speed control algorithm based on full doubly-fed induction machine model has been investigated. Experimental testing of the doubly-fed induction machine control algorithm with matrix converter at rotor side has been performed. Speed control algorithm of the doubly-fed induction machine has been implemented in real time using DSP-controller and successfully tested on the experimental rig.